Hubungan antara panjang tungkai dan tinggi badan dengan kecepatan lari jarak pendek 60 meter pada siswa SMP Negeri 3 Kota Ternate - Gobel, Rusdi; Saiman, Rifaid (PT Mediatama Zayna Indonesia, 2023)
Leg length and height are factors that greatly help a runner to get maximum speed so that the running results will be perfect. The purpose of this study was to determine the relationship between leg length, speed, height and 60-meter short distance running in students of SMP Negeri 3 Ternate. Using a correlational research method with the aim of determining the relationship between independent and dependent variables. The sample consisted of 30 students with a simple rundown sampling technique. The results of the study are as follows: (1) there is a significant relationship between leg length and the 60-meter short-distance running speed of students at SMP Negeri 3 Ternate City with a correlation coefficient value of -0.749. (2) there is a significant relationship between height and the 60-meter short-distance running speed of students at SMP Negeri 3 Ternate City with a correlation coefficient value of -0.779. (3) there is a significant relationship between leg length and height and the 60-meter short-distance running speed of students at SMP Negeri 3 Ternate City with a correlation coefficient value of 0.779.